The Effect of Centrifugation Test on the Physical Stability of Nanoemulsion Containing a Combination of Poloxamer 407, Tween 80, PEG 400, and DMSO - A. Unga, Rani Orelia; Tuloli, Teti Sutriyati; Paneo, Mohamad Aprianto; Aman, La Ode; Mustapa, Mohamad Adam (Jurnal Literasi Mandiri, 2026)
The development of nanoemulsion-based drug delivery systems has gained significant attention due to their ability to enhance drug solubility, stability, and therapeutic effectiveness. Optimizing the combination of surfactants, co-surfactants, and penetration enhancers is essential to produce a kinetically stable nanoemulsion system. This study aimed to formulate and evaluate the physical stability of nanoemulsions prepared using Tween 80, PEG 400, Poloxamer 407, and dimethyl sulfoxide (DMSO), and to determine the optimal formulation based on physicochemical characteristics and accelerated stability testing. Four nanoemulsion formulations (F1–F4) were prepared with varying concentrations of surfactant and co-surfactant. The formulations were evaluated for organoleptic properties, emulsion type, pH, viscosity, and physical stability using a centrifugation test at speeds up to 8000 rpm to detect phase separation, flocculation, or coalescence. The results showed that all formulations were classified as oil-in-water (o/w) nanoemulsions. No phase separation was observed after centrifugation, indicating good physical stability. However, F1 and F2 appeared turbid, whereas F3 and F4 demonstrated better clarity and overall stability. The pH values ranged from 6.6 to 7.4, which are acceptable for topical application, and viscosity values ranged from 405 to 427 cPs, indicating suitable rheological properties for topical use. In conclusion, the combination of Tween 80, PEG 400, Poloxamer 407, and DMSO successfully produced a kinetically stable nanoemulsion system. Among the tested formulations, F3 and F4 exhibited the most optimal characteristics and show strong potential for further development in pharmaceutical nanoemulsion formulations.